A Study on College Students’ Media Literacy in Henan Province under We Media Era - Ling Ling Lu (IJRDO- Journal of Educational Research, 2019)
The rapid development of media information technology has caused the change of media form. Especially with the rapid development and widespread use of APP software, some college students have become psychologically dependent on the use of self-media, and their learning lifestyles and ideas have changed dramatically. Therefore, media literacy education has increasingly become an important part of the comprehensive literacy of college students in we media era. Taking Anyang Normal University as an example, this paper makes a questionnaire survey on media literacy of freshmen to seniors in order to grasp the media literacy status of college students. Then, this paper seeks the characteristics and problems of college students’ media literacy from the aspects of college students’ media contact, the ability to choose we media information and the ability to react to speculation, the creation of media and the production capacity of we media, and so on. Next, this article actively explores ways to cultivate and enhance the media literacy of college students from different levels of government, society, schools, families and individuals.